1997
DOI: 10.1182/blood.v89.11.4128
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human T Cells by Major Histocompatability Complex Class II Expressing Neutrophils: Proliferation in the Presence of Superantigen, But Not Tetanus Toxoid

Abstract: The primary function of polymorphonuclear neutrophils (PMN) in the immune response appears to be acute phagocytic clearance of foreign pathogens and release of inflammatory mediators. Consistent with their assumed lack of major histocompatibility complex (MHC) class II expression, PMN have not been considered to play a role in antigen presentation and T-cell activation. However, recent reports have shown that human PMN can express MHC class II molecules both in vitro and in vivo after stimulation with either g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 30 publications
5
83
1
2
Order By: Relevance
“…However, the donor dependent IFN-γ mediated HLA-DR regulation in isolated neutrophils from healthy donors in vitro refutes this possibility. We even suggest that discrepant results reported on the in vitro regulation of MHC class II molecules via IFN-γ in studies with small numbers of healthy donors originate from the mechanisms described herein [12,19,20,27,28]. Different expression levels of HLA-DR on neutrophils during rhIFN-γ treatment could be explained by donor dependent pharmacokinetics of IFN-γ or by diverse induction of secondary mediators such as GM-CSF and IL-3, both known to regulate MHC class II molecules on these cells [12,13,17].…”
Section: Hd Hd R R Nr Nrmentioning
confidence: 68%
See 1 more Smart Citation
“…However, the donor dependent IFN-γ mediated HLA-DR regulation in isolated neutrophils from healthy donors in vitro refutes this possibility. We even suggest that discrepant results reported on the in vitro regulation of MHC class II molecules via IFN-γ in studies with small numbers of healthy donors originate from the mechanisms described herein [12,19,20,27,28]. Different expression levels of HLA-DR on neutrophils during rhIFN-γ treatment could be explained by donor dependent pharmacokinetics of IFN-γ or by diverse induction of secondary mediators such as GM-CSF and IL-3, both known to regulate MHC class II molecules on these cells [12,13,17].…”
Section: Hd Hd R R Nr Nrmentioning
confidence: 68%
“…Due to the abundance of neutrophils in various inflammatory reactions the expression of HLA-DR on these cells could be essential in diseases, in which superantigens may contribute to pathogenesis such as rheumatic fever or inflammatory bowel disease [21]. Donor dependent variations in inducible HLA-DR expression on neutrophils may influence the course of these diseases as levels of neutrophil MHC class II expression and the magnitude of T cell responses are correlated functions [19].…”
Section: Introductionmentioning
confidence: 99%
“…While the data on MHC class II expression and presentation of SEE by PMN are in agreement with previous ®ndings, 17 . there is discrepancy with respect to presentation of peptide antigens.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 These expressed MHC II molecules have even been shown to be at least partly functional, as the PMNs have been demonstrated to act as required accessory cells during T-cell activation with staphylococcal enterotoxin, a superantigen that does not require intracellular processing prior to presentation. 17 MHC II-expressing PMNs have also been shown to produce interleukin (IL)-8 when stimulated with this same superantigen. 20 The ability to fully process and present more fully processed antigens, such as tetanus toxoid, remains controversial.…”
Section: Mhc II Expressionmentioning
confidence: 94%
“…In vitro experiments with PMNs may be casting doubt on this assumption, as a number of investigators have now reported that PMNs express MHC II on the cell surface when stimulated with IFN-c or other pro-inflammatory stimuli, such as GM-CSF. [16][17][18] CD80 and CD86, costimulatory molecules required for T-cell activation, have also been shown to be up-regulated under the same conditions as induce MHC II expression. 18,19 These expressed MHC II molecules have even been shown to be at least partly functional, as the PMNs have been demonstrated to act as required accessory cells during T-cell activation with staphylococcal enterotoxin, a superantigen that does not require intracellular processing prior to presentation.…”
Section: Mhc II Expressionmentioning
confidence: 99%